Contributions to the knowledge of pitvipers (Viperidae, Gloydius) in the Democratic People’s Republic of Korea: identification, description of specimens, and geographical distribution - Yucheol Shin; Siti N. Othman; Dallin B. Kohler; Irina Maslova; Kevin R. Messenger; Amaël Borzée (ZooKeys)
Basic knowledge of species distribution and diversity is crucial for broader studies of ecology, evolutionary biology, and conservation. However, a basic inventory of species diversity is difficult to obtain in nations that are inaccessible for fieldwork, such as the Democratic People’s Republic of Korea (DPR Korea). The diversity and distribution of snake fauna of DPR Korea are described in only a few publications, and no physical specimens have been examined recently. Here, the first detailed descriptions of pitvipers of the genus Gloydius from DPR Korea are provided, based on four specimens purchased from a market as “snake liquor.” Morphological and genetic data were analyzed to identify these specimens at the species level. Ecological niche modeling was also implemented to estimate the geographical distributions of Gloydius within DPR Korea. Phylogenetic analyses of the mitochondrial 12S rRNA gene fragments identified the samples to three species: G. ussuriensis, G. brevicauda, and G. intermedius. The results of multivariate morphological analyses and diagnostic scalation and body patterns were also congruent with molecular identifications. The niche models had high predictive performance and predicted suitable habitats that were consistent with the ecology of the three species. With this study, the first morphological and genetic data for Gloydius from DPR Korea is provided that can be incorporated into future studies. In addition, the predicted distribution of Gloydius within DPR Korea can be used to map the snakebite risk in the nation. Our study adds to the efforts towards a better understanding of the herpetofauna of DPR Korea.